Financial Feasibility of Precision Agriculture in Smallholder Oil Palm Plantations - Nugra Irianta Denashurya; Singgih Tiwut Atmojo; Muhamad Noor Azizu (Mandalika Journal of Business and Management Studies, 2026)
Smallholder oil palm plantations play a vital role in Indonesia’s rural economy; however, these enterprises remain highly vulnerable to Fresh Fruit Bunch (FFB) price volatility and fluctuations in fertilizer input costs. This study aims to analyze the financial feasibility of transitioning toward precision agriculture and to formulate investment risk mitigation strategies for smallholder oil palm farmers. Using a Systematic Literature Review (SLR) approach and financial meta-analysis, the study evaluates the parameters of Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit-Cost Ratio (Net B/C). Financial projections were synthesized from recent empirical studies on smallholder oil palm farming and precision agriculture adoption, using standardized assumptions regarding technology investment costs, fertilizer-use efficiency, and operational expenditures. The synthesis results indicate that although the initial investment in precision technologies—such as drone mapping and soil nutrient sensors—is relatively high, operational cost optimization, particularly through fertilizer efficiency reaching 15–20%, generates a positive NPV and an IRR substantially exceeding prevailing market interest rates. Further sensitivity analysis demonstrates that business models adopting precision agriculture exhibit greater resilience when facing FFB price declines of up to 25% compared with conventional models. These findings highlight the necessity of supply chain financing interventions from palm oil mills (PKS) or financial institutions to facilitate the initial technology capital costs for smallholder farmers.